2013
DOI: 10.3329/bioethics.v4i2.16375
|View full text |Cite
|
Sign up to set email alerts
|

Research involving Human Subjects - Ethical Perspective

Abstract: Research involving human subjects are important to develop new therapeutics for the betterment of the human race. To take part in such research as volunteers is moral duty of any human. But such experiments should be justifiable and minimal risky for the participants. History of unethical research involving humans led to the development of many guidelines to make such research ethical as well as to gain maximum possible output. Several guidelines have been formulated to ensure research with human participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…The antimicrobial activity of seedless breadfruit using agar diffusion technique corresponds with the zone of inhibition range of 16.5 to 9 mm reported by Fakruddin et al (2012) against Gram positive B. subtilis using the same solvent (ethanol). Antimicrobial activity of seedless breadfruit leaves extracts using agar dilution technique showed that the ethanol extract had a higher inhibitory activity against the test organisms used for the analysis than the n-hexane and water extracts as compared to the two methods used for the antimicrobial analysis, agar dilution technique proved to be a better method as compared to the agar diffusion technique in the present study.…”
Section: Antimicrobial Activity Of Seedless Breadfruitsupporting
confidence: 63%
“…The antimicrobial activity of seedless breadfruit using agar diffusion technique corresponds with the zone of inhibition range of 16.5 to 9 mm reported by Fakruddin et al (2012) against Gram positive B. subtilis using the same solvent (ethanol). Antimicrobial activity of seedless breadfruit leaves extracts using agar dilution technique showed that the ethanol extract had a higher inhibitory activity against the test organisms used for the analysis than the n-hexane and water extracts as compared to the two methods used for the antimicrobial analysis, agar dilution technique proved to be a better method as compared to the agar diffusion technique in the present study.…”
Section: Antimicrobial Activity Of Seedless Breadfruitsupporting
confidence: 63%